4.2 V wearable asymmetric supercapacitor devices based on a VOx//MnOx paper electrode and an eco-friendly deep eutectic solvent-based gel electrolyte. Issue 42 (10th September 2018) - Deng, Ming-Jay; Chou, Tzung-Han; Yeh, Li-Hsien; Chen, Jin-Ming; Lu, Kueih-Tzu
Abstract : A new approach for developing novel energy storage devices involving 3D network VO x and MnO x nanofibers on conductive paper (PVA–acetamide–LiClO4 -graphite/paper, PGP) as electrodes linked with an eco-friendly deep eutectic solvent-based gel electrolyte for SCs is proposed and demonstrated. Abstract : In this work, we successfully fabricated 3D network vanadium oxide (VO x ) and manganese oxide (MnO x ) nanofibers on conductive paper (PVA–acetamide–LiClO4 -graphite/paper, PGP) as electrodes linked with an eco-friendly PVA–acetamide–LiClO4 (PAL) deep eutectic solvent-based gel electrolyte for high-voltage wearable asymmetric supercapacitors (HVWASCs). An ecologically compatible deep eutectic solvent-based electrolyte with self-supporting electroactive species has been generally accepted as a unique type of cost-effective and green electrolyte that possibly involves a bulk concentration of the electroactive species and a large working potential window, thereby achieving a high performance. The HVWASCs are able to work with a large operating voltage of 4.2 V, and supply outstanding energy and power densities (245 W hkg −1 at 0.18 W kg −1 and 95.3 kW kg −1 at 98 W h kg −1 ). The HVWASCs demonstrate remarkable cycling stability and durability after 6000 cycles, including bending and twisting (capacitance retention of 91.5%). The HVWASCs are a superior prospective candidate for wearable/flexible electronic devices and Internet of Things (IoT) applications.